Iron(ii) complexes featuring κ3- and κ2-bound PNP pincer ligands – the significance of sterics. Issue 1 (7th November 2014) - Glatz, Mathias; Bichler, Bernhard; Mastalir, Matthias; Stöger, Berthold; Weil, Matthias; Mereiter, Kurt; Pittenauer, Ernst; Allmaier, Günter; Veiros, Luis F.; Kirchner, Karl
Abstract : A series of octahedral Fe(ii ) complexes of the type [Fe(κ 3 - P, N, P -PNP)(κ 2 - P, N -PNP)X] + (X = Cl, Br) where PNP pincer ligands are coordinated both in a κ 3 - P, N, P - and κ 2 - P, N -fashion was prepared and characterized. Abstract : Treatment of anhydrous FeX2 (X = Cl, Br) with 2 equiv. of the sterically little demanding N, N ′-bisphosphino-2, 6-diaminopyridine based PNP ligands – featuring Ph, biphenol (BIPOL), Me, Et, n Pr, and n Bu substituents at the phosphorus sites and H, Me, and Ph substituents at the N-linkers – afforded diamagnetic cationic octahedral complexes of the general formula [Fe(κ 3 - P, N, P -PNP)(κ 2 - P, N -PNP)X] + featuring a κ 2 - P, N bound PNP ligand. With the sterically more encumbered N -methylated ligand PNP Me -Ph the related complex [Fe(κ 3 - P, N, P -PNP Me -Ph)(κ 2 - P, N -PN HMe -Ph)Cl] + rather than [Fe(κ 3 - P, N, P -PNP Me -Ph)Cl2 ] was formed. This reaction was accompanied by P–N bond cleavage, thereby forming the κ 2 - P, N -bound N -diphenylphosphino- N, N ′-methyl-2, 6-diaminopyridine ligand. In contrast, with the N -phenylated ligands PNP Ph -Et and PNP Ph - n Pr, despite small Et and n Pr substituents at the phosphorus sites, complexes [Fe(κ 3 - P, N, P -PNP Ph -Et)Cl2 ] and [Fe(κ 3 - P, N, P -PNP Ph - n Pr)Cl2 ] were formed, revealing that sterics can be also controlled by substituent variations at the amino N-sites. Depending on the solvent, complexes featuring κ 2 - P, N -bound ligands undergo facile rearrangement reactions to give dicationic complexes of the type [Fe(κ 3 - P, N, P -PNP)2 ] 2+ where both PNP ligands are bound in a κ 3 - P, N, P -fashion. In the presence of either Ag + or Na + salts as halide scavengers this reaction takes place within a few minutes. The pendant PR2 arm of the κ 3 -κ 2 -complexes is readily oxidized to the corresponding phosphine sulfides upon treatment with elemental sulfur. This was exemplarily shown for [Fe(κ 3 - P, N, P -PNP- n Pr)(κ 2 - P, N -PNS- n Pr)Cl] + . Halide abstraction afforded the dicationic bis-chelated octahedral Fe(ii ) complex [Fe(κ 3 - P, N, P -PNP)2 ] 2+ together with the free SNP ligand rather than [Fe(κ 3 - P, N, P -PNP- n Pr)(κ 3 - S, P, N -PNS- n Pr)] 2+ .